Dynamic body acceleration increases by 20% during flight ontogeny of greylag geese Anser anser. (27th February 2020) - Gatt, Marie Claire; Quetting, Michael; Cheng, Yachang; Wikelski, Martin
Abstract : Despite our knowledge of the biophysical and behavioural changes during flight ontogeny in juvenile birds, little is known about the changes in the mechanical aspects of energy expenditure during early flight development, particularly in migratory species. Here, we investigate in a unique experimental setup how energy expended during flights changes over time beginning with early ontogeny. We calculate overall dynamic body acceleration (ODBA) as a proxy for energy expenditure in a group of hand raised greylag geese Anser anser trained to fly behind a microlight aircraft. We propose two potential hypotheses; energy expenditure either increases with increasing physiological suitability (the 'physical development hypothesis'), or decreases as a result of behavioural improvements mitigating flight costs (the 'behavioural development hypothesis'). There was a significant temporal increase of flight duration and ODBA over time, supporting the 'physical development hypothesis'. This suggests that early on in flight ontogeny behavioural development leading to flight efficiency plays a weaker role in shaping ODBA changes than the increased physical ability to expend energy in flight. We discuss these findings and the implications of flight development on the life history of migratory species.